Metacognitive Learning Strategies For The Acquisition Of Cognitive And Methodological Competencies Of The Arabic Language/ Ø§Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ§Øª Ø§Ù„ØªØ¹Ù„Ù… Ù…Ø§ÙˆØ±Ø§Ø¡ Ø§Ù„Ù…Ø¹Ø±ÙÙŠØ© ÙˆØ£Ø«Ø±Ù‡Ø§ ÙÙŠ Ø§ÙƒØªØ³Ø§Ø¨ Ø§Ù„ÙƒÙØ§Ø¡Ø§Øª Ø§Ù„Ù…Ø¹Ø±ÙÙŠØ© ÙˆØ§Ù„Ù…Ù†Ù‡Ø¬ÙŠØ© Ù„Ù…Ø§Ø¯Ø© Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Merkoune, Hiba (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The study aimed to uncover the effect of using metacognitive learning strategies on the acquisition of cognitive and methodological competencies for the Arabic language subject for the high school learner, which is a field study in a group of Algerian high schools, and this by addressing the theoretical heritage, relying on the descriptive approach, and applying study tools, which are two measures of strategies Learning beyond cognitive and Arabic language competencies. On the study sample (300) learners. And it was a simple random sample, the information obtained was collected and statistically treated using statistical techniques (applying the spss program and the T-test), and it was analyzed and a set of results were extracted represented in: The presence of a statistically significant difference between the mean of the group of students with low use and high use of the strategies: learning Metacognitive (all), the monitoring strategy, and the evaluation strategy on the scale of Arabic language competencies for the benefit of those with high use.